Investigating relation of photovoltaic factors with properties of perovskite films based on various solvents. (March 2016) - Tang, Zeguo; Tanaka, Soichiro; Ito, Seigo; Ikeda, Shigeru; Taguchi, Kozo; Minemoto, Takashi
Abstract: Methylammonium lead iodide (MAPbI3 ) perovskite solar cells are fabricated by two-step sequential deposition processes. The influence of the properties of PbI2 precursor film on the cell performance is investigated based on different solvents. The X-ray diffraction (XRD) patterns, Urbach energy value and scan electron microscope (SEM) images reveal that solvents have considerable influence on the crystal structure, band tail and morphology of PbI2 precursor films. The addition of a small amount of dimethyl sulfoxide (DMSO) in N, N -dimethylformamide (DMF) solvent promotes the compactness and uniformity of PbI2 precursor films, but also causes defect in band tail. The relation of the properties of perovskite film with photovoltaic parameters is explored. A high conversion efficiency of 16.6% for solar cells based on mixed solvents with 10 vol% DMSO is achieved. Meanwhile, light beam-induced current (LBIC) images directly evidence the improvement of uniformity for perovskite solar cells caused by DMSO addition. Graphical abstract: Highlights: PbI2 films show critical influence on performance of perovskite solar cells. The addition of DMSO in DMF improves the compactness and uniformity of PbI2 films. High efficiency of 16.6% is achieved based on mixed solvents. High uniformity is confirmed by LBIC measurement.